Pengaruh Promosi Dan Pengetahuan Terhadap Minat Melakukan Transaksi di Bank Syariah - Nur Afif Jalaludin; Purwanto, Tinggal; Aswin (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study aims to determine the influence of promotion and knowledge on the interest of women from recitation groups in Kelapa District to conduct transactions at Islamic Banks. The type of research used is quantitative research with a sample of 161 respondents. With the data measurement technique using the Likert scale. The data was processed through the SPSS program version 25.0 with multiple linear regression analysis techniques. The research results show that: 1) Promotion partially affects the interest in conducting transactions at Islamic Banks with a t-calculated value (7.407) < t-table (1.654) or a significance value of 0.000 < 0.01. 2) Knowledge partially affects the interest in conducting transactions at Islamic Banks with a t-calculated value (3.268) > t-table (1.654) and a significance value of 0.000 < 0.01.